Digit ratio (2D:4D), impulsiveness and aggression in male heroin addicts: A prospective controlled study. (15th October 2017) - Cicek, Ismet Esra; Cicek, Erdinc; Demirel, Başak; Ayhan, Medine Gıynaş; Varsak, Nalan; Özbek, Seda Yıldırım; Selçuk, Mahmut; Eren, Ibrahim
Abstract: The ratio of the length of the index finger to ring finger (2D:4D) is considered to be an indicator of prenatal testosterone exposure. The androgen theory suggests that the masculinizing effects of fetal androgens may play a role in certain psychiatric disorders. We have examined the relationship between impulsiveness, aggression and adult attention deficit along with the 2D:4D digit ratios in male heroin abusers. The study included 62 male patients with heroin dependence and a control group comprising of 50 healthy individuals having similar socio-demographic features. Scores of the Barratt impulsiveness scale, Buss Perry Aggression Scale and attention deficit hyperactivity disorder (ADHD) self-report scale were obtained from the participants. The lengths of second and fourth digits of the right hands were measured. The patients group had significantly higher scores of impulsiveness, aggression and ADHD compared to the healthy control group; and their digit ratios were significantly lower. No correlations were found between digit ratios of heroin addicts and their impulsiveness, aggression and ADHD scores. Our study is the first to examine the relationship between digit ratio and impulsiveness, aggression and ADHD levels in patients with heroin dependence. Prenatal high testosterone exposure might have a role in the etiology of heroin addiction. Highlights: We examined the 2D:4D digit ratios in male heroin abusers. The patients' digit ratios were significantly lower than controls. The patients had significantly higher scores of impulsiveness, aggression and ADHD. Prenatal high testosterone exposure might have a role in the etiology of heroin addiction.